Impact of parents' nutritional knowledge on the nutrition and frequency of consumption of selected products in children and adolescents practicing football in a football club in Bydgoszcz, Poland - Monika Anna Ameryk; Maciej Świątkowski; Piotr Sikorski; Agnieszka Augustyniak; Małgorzata Szamocka (Kazimierz Wielki University, 2017)
Ameryk Monika, Świątkowski Maciej, Sikorski Piotr, Augustyniak Agnieszka, Szamocka Małgorzata. Impact of parents' nutritional knowledge on the nutrition and frequency of consumption of selected products in children and adolescents practicing football in a football club in Bydgoszcz, Poland. Journal of Education, Health and Sport. 2016;6(11):456-472. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.179146 http://ojs.ukw.edu.pl/index.php/johs/article/view/4020       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 28.11.2016.       Impact of parents' nutritional knowledge on the nutrition and frequency of consumption of selected products in children and adolescents practicing football in a football club in Bydgoszcz, Poland   Monika Ameryk, Maciej Świątkowski, Piotr Sikorski, Agnieszka Augustyniak, Małgorzata Szamocka   Department of Gastroenterology and Nutrition Disorders, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń   Correspondence: Monika Ameryk, Department of Gastroenterology and Nutrition Disorders, Collegium Medicum in Bydgoszcz, Ujejskiego 75, 85-168 Bydgoszcz, Poland, Tel: +48 692 222 855. E-mail: monika.ameryk@gmail.com       Abstract Rational diet improves the ability for intensive effort and training. Nutrition in children and adolescents depends on the nutritional knowledge of their parents. The aim of the study was to assess the parents' nutritional knowledge and its impact on the nutrition of their children practicing football. Study group consisted of 100 football players aged 11-16. The parents' nutritional knowledge and the nutrition of the athletes were assessed using the modified KomPAN questionnaire. The correlation between the parents' knowledge and the frequency of consumption of selected products was determined using a χ2 test in the Statistica 12.5 software. A correlation between the parents' nutritional knowledge and the frequency of consumption of selected products by their children was observed. Parents with insufficient knowledge less frequently served dark bread and thick groats than those with good and sufficient knowledge. Parents with good and sufficient knowledge less frequently served instant soups, canned meat, energy and isotonic drinks. No impact of the parents' knowledge was observed with reference to white cheese, vegetable oils and sweets. Nutritional education of the parents of young athletes is necessary regardless of their nutritional knowledge. Improving eating habits can positively affect children's development and achievements in sports.   Keywords: Nutrition; Knowledge; Sport; Young Athletes; Eating habits.